Demographic analysis of foreign visitors to the EXIT festival, Novi Sad - Bjeljac Željko; Lović Suzana (Zbornik Radova: Geografski institut "Jovan Cvijić", 2011)
In this paper we studied the habits and behaviour of visitors of EXIT tourist event in Novi Sad. The research was conducted on a sample of 189 randomly selected respondents from abroad. The aim was to determine whether there is a difference in the motives of foreign tourists coming to EXIT, a selection of vehicles, as well as the use of various means of tourist propaganda and the structure of expenditure of funds at foreign visitors. EXIT festival, Novi Sad has been selected for the survey because of growing brand of the festival in the total tourist offer of Serbia, specific groups of visitors, the number of foreign tourists, the links with the locality of maintaining.